Aortic Elasticity and Cardiovascular Risk Stratification: A Narrative Review on the Current Understanding - Niya Mileva; Tsvetelina Velikova; Toni Velikov; Dobrin Vassilev (Journal of Vascular Diseases, 2024)
Cardiovascular risk stratification is a cornerstone of preventive cardiology, aiming to identify individuals at a higher risk for adverse events. In line with this, aortic elastic properties have gained recognition as crucial indicators of vascular health and predictors of cardiovascular outcomes. This narrative review delves into the significance of aortic stiffness, compliance, and distensibility in risk assessment, shedding light on their associations with cardiovascular diseases, such as hypertension, atherosclerosis, and coronary artery disease. This review aims to provide an overview of the current knowledge regarding aortic elastic properties and their role in cardiovascular risk stratification. The exploration of potential mechanisms and clinical implications outlines the need for further research to establish precise links between aortic elasticity and cardiovascular risk. Furthermore, the integration of advanced imaging, genetic factors, and personalized medicine is suggested to refine risk assessment strategies and enhance patient care. Ultimately, this review underscores the importance of aortic elastic properties in cardiovascular risk prediction, opening avenues for future research and clinical application.